The Leadership Style Effect on The Job Satisfaction and The Performance - Rahmat, Rahmat; Ramly, Mansyur; Mallongi, Syahril; Kalla, Rastina (Asia Pacific Journal of Management and Education (APJME), 2019)
This study aims to analyze the leadership style effect on job satisfaction, the leadership style effect on performance, the job satisfaction effect on performance and the leadership style through job satisfaction effect on performance. The results of the regression analysis show the equation: Y1 = 0.740X and Y2 = 0.226X + 0.601Y1. The path analysis results show the equation, Y2 = 0.671X. Hypothesis test results indicate that the leadership style has a significant positive effect on job satisfaction, the leadership style has a significant positive effect on performance, the job satisfaction has a significant positive effect on performance and the leadership style through job satisfaction significant positive effect on performance. Keywords: Leadership style, job satisfaction, performance.